Resurgence of human coronavirus OC43 at a long-term care facility during the coronavirus disease 2019 (COVID-19) pandemic: Outbreak investigation - Koji Ohyama; Hitoshi Honda; Momoko Aoki; Mitsutaka Wakuda; Tomoaki Kitahara; Chisaki Kaede; Yohei Doi; Yuki Uehara (Cambridge University Press, 2023)
The incidence of seasonal infections due to respiratory viruses other than severe acute respiratory coronavirus virus 2 (SARS-CoV-2) has declined due to heightened public infection prevention measures against coronavirus disease 2019 (COVID-19). We describe an outbreak of human coronavirus OC43 infection that occurred at a long-term care facility and whose clinical features were indistinguishable from COVID-19.